2018
DOI: 10.1080/01621459.2017.1323640
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Probing “Don’t Know” Responses on Measurement Quality and Nonresponse in Surveys

Abstract: In survey interviews, "Don't know" (DK) responses are commonly treated as missing data. One way to reduce the rate of such responses is to probe initial DK answers with a follow-up question designed to encourage respondents to give substantive, non-DK responses. However, such probing can also reduce data quality by introducing additional or differential measurement error. We propose a latent variable model for analyzing the effects of probing on responses to survey questions. The model makes it possible to sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The removal of 'Don't know' options from attitudinal scales has been shown to encourage some respondents to provide directional responses that they would have otherwise withheld, but which were consistent with answers given to questions about similar issues when a 'Don't know' option was included (Bradburn and Sudman, 1988;Gilljam and Granberg, 1993). Research by Kuha et al, (2018) has revealed how follow up probes can help respondents give a directional response. However there is a time cost to this and there can be a measurement effect as the probe can affect the response given.…”
Section: Introductionmentioning
confidence: 88%
“…The removal of 'Don't know' options from attitudinal scales has been shown to encourage some respondents to provide directional responses that they would have otherwise withheld, but which were consistent with answers given to questions about similar issues when a 'Don't know' option was included (Bradburn and Sudman, 1988;Gilljam and Granberg, 1993). Research by Kuha et al, (2018) has revealed how follow up probes can help respondents give a directional response. However there is a time cost to this and there can be a measurement effect as the probe can affect the response given.…”
Section: Introductionmentioning
confidence: 88%
“…Researchers may probe survey participants that "do not know" to obtain more information from those participants that might have been too comfortable to answer seriously in the first round. However, follow-up probing questions may lead to a distorted measure of what people truly think about future inflation, see Kuha et al (2018). In some application, it make sense to omit the "do not know" option from the list of possible answers.…”
Section: Uncertainty About Inflation Target Credibilitymentioning
confidence: 99%
“…First, in cases where respondents have difficulties in understanding a question, interviewers can clarify questions and answer options, thus helping respondents to provide a valid answer. Second, interviewers may actively probe and argue in order to obtain valid responses (Kuha et al 2014). Third, many respondents likely perceive that not providing an answer is an undesired behavior in front of the interviewer because it runs counter to the main purpose of the interview of collecting valid information.…”
Section: Mode Effectsmentioning
confidence: 99%